2020
DOI: 10.1080/19475683.2020.1720290
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian spatial shared component model for identifying crime-general and crime-specific hotspots

Abstract: The spatial patterning of crime hotspots provides place-based information for the design, allocation, and implementation of crime prevention policies and programmes. However, most spatial hotspot identification methods are univariate, analyse a single crime type, and do not consider if hotspots are shared amongst multiple crime types. This study applies a Bayesian spatial shared component model to identify crime-general and crime-specific hotspots for violent crime and property crime at the small-area scale. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 79 publications
1
27
0
Order By: Relevance
“…This study aimed to analyze whether there was a shared spatial distribution of police calls reporting street-level crime and IPVAW. A Bayesian joint model was performed in line with previous research that incorporates a multivariate spatial analysis to study crime outcomes [40][41][42][43]51,52]. In addition, two different Poisson regression models were conducted to assess the spatial similarity of relative risks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study aimed to analyze whether there was a shared spatial distribution of police calls reporting street-level crime and IPVAW. A Bayesian joint model was performed in line with previous research that incorporates a multivariate spatial analysis to study crime outcomes [40][41][42][43]51,52]. In addition, two different Poisson regression models were conducted to assess the spatial similarity of relative risks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, police calls do not distinguish between single and multiple calls referring to the same incident and/or the same actors, which leads to a possible data dependency bias [24]. Other useful measures such as police-report records of criminal offenses [21,24,41,66], assaults resulting in hospitalizations [12], IPV-related medical records and hospitalizations [38], and self-reported IPV were not available. In addition, violence behind closed doors was measured using IPVAW; however, other IPV types, such as violence perpetrated by female partners or same-sex couples were not incorporated in this analysis, and thus the results are not generalizable to those types of IPV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study by Law et al (2020), they followed the approach put forward by Anselin et al (2000) and utilised Bayesian multivariate spatial models to identify general and crime specific hotspots in Ontario, Canada. Their research showed evidence demonstrating that crimes are concentrated; therefore, the majority of crime-general clusters had very strong evidence of being a hotspot.…”
Section: Crime and House Pricesmentioning
confidence: 99%
“…It has been used to identify the impact of economic, social, and demographic factors on the spatial variability of the household share of economic distress [51]; identify the spatial structure of the calls to the Portuguese health line, accounting for the demographics, socio-economic information, and characteristics of the health systems [52]; identify clustering in severe mobility crash risk and diagnosing of active transportation safety issues [53]. Moreover, it has been employed in the analysis of spatial patterns and hotspot detection of violent and property crimes at a small spatial scale in Toronto, Canada [54]; map the main features of fertility, such as timing, pace, and scale, and to detect spatial disparity in fertility transition in Brazil [55].…”
Section: Spatial Statistics Fields Of Applicationmentioning
confidence: 99%